Influence Of Information Technology, Information Sharing, And Trust On Supply Chain Performance, Mediated By Integration In Batam City's Retail Sector - Melissa Melissa; Immanuel Zai (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to analyze the impact of information technology, information sharing, and trust on supply chain performance, with supply chain integration as a mediating variable. The research method used is a quantitative approach, with questionnaires distributed to 236 individuals in the retail supply chain in Batam. Data were analyzed using the PLS method with SmartPLS 3.0. The results show that information technology and trust have a significant positive relationship with supply chain performance. Additionally, supply chain integration strengthens the relationships between information technology, information sharing, trust, and supply chain performance. However, it was found that information sharing does not have a significant relationship with supply chain performance. The implications of this study highlight the importance of effective use of information technology to enhance supply chain integration, which in turn strengthens information sharing and trust among partners, thereby improving retail performance in Batam City.